Empowering college student employment through community cultural wealth: a case study of human resource management students in China - Yang, Fan (Frontiers in Education, 2025)
The global economic slowdown, the expansion of higher education, compounded by social factors such as the COVID-19 pandemic and the significant contraction of key employment industries, along with personal and institutional factors, have collectively created multiple challenges for college students in their employment pursuits, affecting both internal competencies and external opportunities. This article explores how Community Cultural Wealth empowers a group of Human Resources Management major college students in their job-seeking endeavors in China. Using a case study approach, this research employed document analysis and one-to-one interviews with seven student participants and four teacher participant at a university in Beijing. In addition, the researchers collected surveys from 77 senior students major in Human Resources Management at the research site university in the class of 2025 to understand the current situation of student employment. Through the lens of the Community Cultural Wealth framework, the findings revealed that successful employment was achieved by leveraging social capital from human resource managers, mentors, peers, alumni, and friends. Participants established clear career plans and aspirations, navigated diverse on-campus and off-campus resources, received material and emotional support from familial networks, and exercised resistance capital when facing employment discrimination. Additionally, this study offers actionable strategies and recommendations for job-seeking students, professional mentors, university administrators, and policymakers addressing this issue.